A case study on a job rotation program for Agro Bank Melaka / Nurhidayah Othman - Othman, Nurhidayah (Faculty of Business and Management, 2009)
This study is about the issue of a job the rotation program that suitable for Agro Bank Melaka. In this study, it involves the three elements for a job rotation program which is the background information, the program and the guidelines. The three elements also would help Agro Bank Melaka to choose the right job rotation program for the organization to implement. For the data collection method, the researcher chooses to use both types which are the primary and the secondary data. The primary data source that the researcher selects is interview. The researcher had done direct interview to the client service officer of Agro Bank Melaka, Puan Lamisah Binti Hassan to get information about the job rotation program at Agro Bank Melaka. For the secondary data, the researcher chooses to use from two sources which are the internal and external sources. For internal secondary data source, the researcher gets the information from Agro Bank website and intranet. Whereas, for the external information, the researcher gets from a few sources such as books, journals, articles, and reports. The findings of this study is the organization practices relating to the issue, a few sets of job rotation programs that Agro Bank Melaka should consider and a set of job rotation program that proposed by the researcher for the organization. Lastly is the recommendations for Agro Bank Melaka relating to the issue based on the finding of the study.